2011
DOI: 10.1136/gutjnl-2011-301153
|View full text |Cite
|
Sign up to set email alerts
|

TPX2andAURKApromote 20q amplicon-driven colorectal adenoma to carcinoma progression

Abstract: Background and objective Progression of a colorectal adenoma to invasive cancer occurs in a minority of adenomas and is the most crucial step in colorectal cancer pathogenesis. In the majority of cases, this is associated with gain of a substantial part of chromosome 20q, indicating that multiple genes on the 20q amplicon may drive carcinogenesis. The aim of this study was to identify genes located on the 20q amplicon that promote progression of colorectal adenoma to carcinoma. Design Functional assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 43 publications
5
58
1
Order By: Relevance
“…Usually, large fragments of the 20q arm are amplified as a whole, suggesting a role of multiple 20q genes on CRC progression. Recently, we confirmed by functional analyses that multiple genes on chromosome 20q contribute to cancer processes [9]. AURKA and TPX2 were identified as genes that promote 20q gain-driven colorectal adenoma-to-carcinoma progression.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Usually, large fragments of the 20q arm are amplified as a whole, suggesting a role of multiple 20q genes on CRC progression. Recently, we confirmed by functional analyses that multiple genes on chromosome 20q contribute to cancer processes [9]. AURKA and TPX2 were identified as genes that promote 20q gain-driven colorectal adenoma-to-carcinoma progression.…”
Section: Introductionsupporting
confidence: 53%
“…The 20q amplicon harbors multiple genes that contribute to CRC carcinogenesis as indicated by the large part of the chromosome arm that is generally amplified in CRC. We recently identified AURKA and TPX2 as major contributors to 20q gain associated CRC progession [9]. In the same study CSE1L, DI-DO1 and RBM39 were also found to contribute to several cancer-related biological processes such as cell viability and anchorage-independent growth.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Five microarrays were selected, which included CRC cases, colorectal adenoma cases, and normal tissues. CRC commonly arises from normal colorectal tissue that develops into adenomas [28]. Of 142 differentially expressed lncRNAs, 15 candidates were selected.…”
Section: Discussionmentioning
confidence: 99%